ANALISIS FRAMING PEMBERITAAN WAJIB TES PCR DI MEDIA ONLINE TVONENEWS.COM DAN KOMPAS.COM - Rizkya Seftiyana; Rini Ganefwati; Ita Nurlita (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
This study discusses the analysis of mandatory news framing for the PCR test in the online media tvonenews.com and kompas.com. starting from the government which has taken various ways to stop the spread of this virus, then health workers who are at the forefront to cure people who have been positively affected by Covid-19 and also all Indonesian people. The media certainly have their own way of looking at their own point of view and judgment in framing, viewing and presenting news. Online media are also very aggressive in providing information regarding the development of this regulation, namely tvonenews.com and kompas.com. This study uses qualitative research and Robert N. Entrman framing analysis. This study aims to determine how the framing is carried out by the two media in the mandatory reporting of the PCR (Polymerase Chain Reaction) test. Tvonenews.com when writing the title tends to be more easily accepted by the reader. Kompas tends to be bolder, so just by looking at the title, readers will think that kompas.com are criticizing the government. There are several news stories that have almost the same content even though the packaging is between tvonenews.com and kompas.com. The approach to see how reality is shaped and constructed by the media, the end result is that there is a certain part of reality that is more prominent and easier to recognize. Framing analysis (Eriyanto, 2002: 4) is one of the methods of text analysis which is in the category of constructionist research.